Intrinsic permeabilities of transparent soil under various aqueous environmental conditions. Issue 3 (9th August 2022) - Yan, G.; Shi, H.; Ma, Y.; Scheuermann, A.; Li, L.
Abstract : This study investigated the intrinsic permeability of two water-based transparent soil surrogates (Aquabeads and hydrogel beads) in various aqueous environments. To maximise the efficiency of seepage tests for different solutes (salt and a surfactant) at different concentrations, a rapid approach was established to estimate the intrinsic permeabilities of these water-based granular polymers. Because of the geometric similarity of the pore structures formed by the packing of granular polymer beads of different sizes, the Kozeny–Carman permeability estimation can be directly applied to study the permeability ( K ), which primarily varies with the effective diameter ( de ). A systematic sieving analysis of these polymers was conducted to determine the values of both de and K . The experimental results showed that both parameters monotonically decrease with increasing solute concentration. The critical shrinkage concentrations for salt and the surfactant were identified as 5–7 ppt and 0.02% (mass/volume), respectively. This work represents the first contribution to providing a sound understanding of the intrinsic permeabilities of these surrogate soils when saturated with various solutions. This work contributes to the physical modelling in geotechnics when using those materials.